Biomass and Bioenergy 2014
DOI: 10.1007/978-3-319-07578-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of Oil Palm Biomass to Value-Added Products

Abstract: Indonesia and Malaysia account for about 85 %

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…In 2013 it was reported that the global production of palm oil was 56 million metric tons. For every metric ton of palm oil produced, 4 tons of dry biomass is generated, of which 12% are OPMF (Geng 2014). Therefore, it is estimated that the global OPMF production in 2013 was 26 million tons.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013 it was reported that the global production of palm oil was 56 million metric tons. For every metric ton of palm oil produced, 4 tons of dry biomass is generated, of which 12% are OPMF (Geng 2014). Therefore, it is estimated that the global OPMF production in 2013 was 26 million tons.…”
Section: Introductionmentioning
confidence: 99%
“…According to Geng [21], ethanol can be produced from oil palm biomass which not only be converted to fuel ethanol, but it can also be further processed into value-added chemicals such as ethylene, polyethylene, ethylene oxide, butanol, butane, butadiene, acetic acid, ethyl acetate, and so on. According to Geng [21], ethanol can be produced from oil palm biomass which not only be converted to fuel ethanol, but it can also be further processed into value-added chemicals such as ethylene, polyethylene, ethylene oxide, butanol, butane, butadiene, acetic acid, ethyl acetate, and so on.…”
Section: Renewable Source For Carbon and Ethanol Productionmentioning
confidence: 99%
“…Furthermore, research development on ethanol production from lignocellulosic components has always been the focus research in many countries owing to the energy crisis and demand for alternative greener fuels. According to Geng [21], ethanol can be produced from oil palm biomass which not only be converted to fuel ethanol, but it can also be further processed into value-added chemicals such as ethylene, polyethylene, ethylene oxide, butanol, butane, butadiene, acetic acid, ethyl acetate, and so on.…”
Section: Renewable Source For Carbon and Ethanol Productionmentioning
confidence: 99%
“…Oil palm arrived in Indonesia by the Dutch in 1848, and some seeds were planted in the Bogor Botanical Gardens [2]. Since 1991, Indonesia has planted oil palm commercially [3]. According to the data from the United States Department of Agriculture (USDA) in 2019, Indonesia has the largest area of oil palm plantations, about 11.75 million ha, followed by Malaysia, Nigeria, Thailand, Colombia, Cote D'Ivoire, Ghana, Guinea, Ecuador, Guatemala and produced palm oil about 42.5 million metric tons.…”
Section: Introductionmentioning
confidence: 99%
“…These can lead to a heavy problem on the environment [6][7][8][9] because of the utilization of those has not been seriously considered. It is still focused on the main product of oil palm (crude palm oil (CPO) and palm kernel oil (PKO)) [3]. This problem can be solved by utilizing these by-products for various applications, such as for reinforcement of composite [10].…”
Section: Introductionmentioning
confidence: 99%